Saliva or Nasopharyngeal Swab Specimens for Detection of SARS-CoV-2 - Wyllie, Anne L; Fournier, John; Casanovas-Massana, Arnau; Campbell, Melissa; Tokuyama, Maria; Vijayakumar, Pavithra; Warren, Joshua L; Geng, Bertie; Muenker, M. Catherine; Moore, Adam J; Vogels, Chantal B.F; Petrone, Mary E; et al. (The New England journal of medicine, 2020)
In this letter, the investigators report that saliva specimens and nasopharyngeal swab specimens had similar sensitivity in the detection of SARS-CoV-2 RNA in both symptomatic and asymptomatic persons.